Inhibitory effects of urine on the polymerase chain reaction for cytomegalovirus DNA. Issue 5 (May 1991) - Khan, G; Kangro, H O; Coates, P J; Heath, R B
Abstract : The inhibitory effects of urine samples taken from neonates and older children, some of which were known to be infected with cytomegalovirus, on the polymerase chain reaction (PCR) were investigated. Urea was the major inhibitory component of urine and inhibited the PCR at a concentration of more than 50 mM. Urine samples from older children were more inhibitory than those from neonates. This correlated with the higher concentration of urea generally found in urine samples from older children compared with neonatal urines. Two of 13 neonatal urine samples, however, were inhibitory despite low urea concentrations--presumably due to metabolites derived from parenteral nutrition. The inhibitory effects of urine were effectively removed by simple dialysis or ultrafiltration. The sensitivity and specificity of PCR for detecting cytomegalovirus DNA in urine were further improved by using "nested" primers and a modified PCR protocol entailing the use of reduced reactants in the first 20 cycles of a two-stage 50 cycle PCR.